Effectiveness of Early Exercise Against Uterine Involution in Spontaneous Postpartum Patients - Nurafifah, Dian; Kusbiantoro, Dadang (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
It is estimated that 50% of puerperal mortality occur within the first 24 hours. At thistime the involution process occured. Involutionary disorders cause complications whichis the leading cause of maternal mortality. Most of postpartum women do not obtainexercise guidance after giving birth. They are only advised to do simple mobilizationwithout planned guidance. The purpose of this study was to determine the effectivenessof early exercise against uterine involution (fundus and lochea). The research methodused Quasi Experimental (pre-post test non equivalent control group design). It wasconducted from May to August 2017. The samples were 40 respondents spontaneousprimiparous postpartum mother. The study was started by 1) divided the samples intocontrol group and treatment group, 2) measured the fundus and lochea, 3) providedearly exercise on treatment group, 4) re-measured fundus and lochea in both groups, 5)analyzed the effectiveness of early exercise to fundus and lochea expenditure decrease.The data analysis used Mann Whitney with ÃŽÂ± = 0.05. The results showed p value is 0.000(fundus) and p value are 0.001 (lochea). It means that early exercise is effective againstuterine involution (fundus and lochea). The results can provide positive contribution inpreventing maternal mortality caused by puerperal complications.